REVIEW ON ANTIBIOTIC RESISTANCE AND ITS MECHANISM OF DEVELOPMENT - Dugassa, Jiregna; Shukuri, Nesrie (Journal of Health, Medicine and Nursing, 2017)
Purpose: Antibiotics are chemical agents that prevent bacterial growth by stopping the bacterial cell from dividing (bacteriostatic) or by killing them (bactericidal). So antibiotics are the integral part of medicines used to insure human and animal health. However, the wide spread use, misuse and overuse of antibiotics in human and animal has raised the concern about the development of resistant bacteria that possess a potential danger to animals and humans. Antibiotic resistant microorganisms have been described as "nightmare bacteria" that "pose a catastrophic threat" to people in every country in the world. So, the aim of this seminar paper is to review on antibiotics resistance and further to recommend on its control measures. Methods: The use of antibiotics in sub therapeutic doses, non-laboratory oriented therapy and poor storage are some of the factors that engender antibiotic resistance. As there are many different mechanisms in which antibiotics can kill or inhibit the growth and multiplication of bacteria, there are also different mechanisms of resistance in which bacteria developed against antibiotics. The use of antibiotics as growth promoters in food animal producers is significant cause for antibiotic resistance in animals. Even today zoonosis of the resistant strains is able to occur and become a risk to human health. There are guidelines in both human and Veterinary Medicine for rational use of antibiotics. Several new initiatives such as vaccines, bacteriocins, competitive exclusions, bacteriophages and others are being put in place to halt and control the alarming trend of resistance to antibiotics. But, there are still some indications on the misuse of antibiotics by health care providers, unskilled practitioners and drug consumers. Thus, awareness creation should be conducted on rational use of antibiotics in veterinary and medical practice to mitigate the occurrence of antibiotic resistance.